GE_GERICHTE P/20642/2016 vom 10. Dezember 2018 - GE Cour de justice (2018)
TRAITEMENT AMBULATOIRE ; MESURE THÉRAPEUTIQUE INSTITUTIONNELLE ; IRRESPONSABILITÉ | CP.63.al1; CP.63.al3; CP.19.al1; CPP.374; CPP.419